2018
DOI: 10.3389/fgene.2018.00526
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Depletion in Elderly Mice Improves Response to Tumor Immunotherapy, Increases Anti-tumor T Cell Activity and Reduces Treatment-Induced Cachexia

Abstract: Most cancers emerge in the elderly, including lung cancer and mesothelioma, yet the elderly remain an underrepresented population in pre-clinical cancer studies and clinical trials. The immune system plays a critical role in the effectiveness of many anti-cancer therapies in young hosts via tumor-specific T cells. However, immunosuppressive macrophages can constitute up to 50% of the tumor burden and impair anti-tumor T cell activity. Altered macrophage phenotype and function during aging may further impact an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 88 publications
3
44
0
Order By: Relevance
“…Identifying the full repertoire of senescent cells in vivo is critical in understanding how their removal might affect a healthy lifespan. There is no doubt that eliminating some senescent cells is beneficial for healthy aging and overall lifespan [78][79][80]. However, there are abundant p16 High senescent cell types in the aging organism that are structurally and functionally important while their removal could have detrimental consequences.…”
Section: Preventing An Age-induced "Leaky Gut"mentioning
confidence: 99%
“…Identifying the full repertoire of senescent cells in vivo is critical in understanding how their removal might affect a healthy lifespan. There is no doubt that eliminating some senescent cells is beneficial for healthy aging and overall lifespan [78][79][80]. However, there are abundant p16 High senescent cell types in the aging organism that are structurally and functionally important while their removal could have detrimental consequences.…”
Section: Preventing An Age-induced "Leaky Gut"mentioning
confidence: 99%
“…Macrophages play a critical role in removing garbage and bacteria, maintaining homeostasis, and regulating inflammation, and undergo various changes with age which can contribute to age-related pathologies, largely by increasing inflammation. Several studies have demonstrated that macrophages can actively drive age-related pathologies, as depleting macrophages led to diminished inflammatory responses and improved survival outcomes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…We first investigated whether aging influenced AE17 mesothelioma tumor growth in young (2–5 months) vs. elderly (20–24 months) C57BL/6J mice, and found that tumors grew faster in elderly mice (Figure 1A) (36). One possibility to account for faster tumor growth is that aging programs a more suppressive immune environment that is reflected by DCs and T cells.…”
Section: Resultsmentioning
confidence: 99%